By their own standards: a new perspective for the question of moral agency in animals - Grattan, Douglas, author; Rollin, Bernard, advisor; Gorin, Moti, committee member; Volbrecht, Vicki, committee member (Colorado State University. Libraries, 2017)
Much of the history of ethology, philosophy, and psychology has been a sort of tug-of-war between those claiming that animals have certain capacities and others claiming that such science is unverifiable and amounts to anthropomorphizing. While resistance to such positive claims has certainly fallen off over the past few decades, the idea that animals can be moral is one of the last bastions of human uniqueness to which many tenaciously hold. Yet in the light of newer research involving emotion and cognition, such claims against morality in animals become harder to defend. However, even those who do claim that animals can possibly act morally still hold back from making the stronger claim that animals can be held responsible for their behavior. I view such attitudes against morality (or moral agency) in animals and against anthropomorphizing in this case as incorrect for the same reason: combined, they assume that 1) if animals are truly moral, they must be moral in the same ways we are, and 2) if they are moral, then they must be viewed in the same way we view humans and therefore treated as such. In short, both claims involve anthropocentrism and worries of anthropomorphism. This work will be dedicated to showing that this point of view is conceptually flawed and suggesting a new avenue to pursue this line of thought, one that keeps in mind both animal uniqueness-- by invoking the subjective lived experiences of the animals themselves, coupled with what they have reason to know—and, surprisingly, human uniqueness.
Keywords: ethics; moral agency; ethology; animals